PERSONALITY, CHARACTERISTICS AND ROLE OF MUSLIM WOMEN IN SOCIETY - Shabana Anjum (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The role and characteristics of Muslim women in society are highly diverse and important. Muslim women face a variety of challenges and opportunities in different cultural, religious and social contexts. Their personality, beliefs, family and their role in society are determined by these different contexts. The contribution of Muslim women to society is not limited to domestic work, but they also actively participate in fields such as education, politics, health, arts, and social service. Views about their rights, freedoms, and social status vary, reflecting not only their piety and cultural heritage, but also their struggles, successes, and aspirations to get an equal place in society. In this article, we will discuss the personality of Muslim women, their rights, their status in society, and the direction of their development.